PENINGKATAN HASIL BELAJAR PADA MATERI DONGENG MENGGUNAKAN MODEL PEMBELAJARAN PAIRED STORYTELLING BERBANTUAN MEDIA GAMBAR SERI PADA SISWA KELAS IV SD NEGERI BLANG ARA - Nadila Isnaini; Nurlaili; Zulkarnaini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low learning outcomes of Indonesian language on fairy tale material in grade IV of Blang Ara State Elementary School, especially because learning is still dominated by lecture methods so that students are less active and do not understand the content of the story. The purpose of this study is to improve learning outcomes, activities, and student responses through the application of the Paired Storytelling learning model assisted by a series of pictures. This study uses Classroom Action Research (CAR) which is carried out in two cycles with 20 fourth grade students as subjects. Data collection techniques include tests, observations, and student response questionnaires. The results of the study showed a significant increase, namely learning completeness increased from 5% in the pre-action to 50% in cycle I, and increased again to 95% in cycle II. Teacher activity also increased from 80% to 88.88%, while student activity increased from 77.77% to 92.22%. Student responses to learning are classified as very good because this model helps them more easily understand fairy tale material and learn actively. Thus, it can be concluded that the application of the Paired Storytelling learning model assisted by a series of pictures is effective in improving Indonesian language learning outcomes in fairy tales in fourth-grade students at Blang Ara State Elementary School.